IMPROVING STUDENTS’ READING COMPREHENSION THROUGH THINK-PAIR-SHARE (TPS) TECHNIQUE - Emi Rosmiati; Mila Nuryani (IKIP Siliwangi, 2020)
Abstract The aim of this research is to improve students' reading comprehension at the eleventh grade of SMA Mathla’ul Anwar using the think-pair-share technique. The writers implementing this method is to make students easier to understand in a reading activity in the class through discussion and sharing information with their friends. The method of the research is classroom action research (CAR), the research has been carried out in three cycles to achieve students’ improvement in reading comprehension. The mean score in the first cycle is 59.6. In the second cycle is 67.5 and the third cycle is 77. The mean score of the third cycle shows that the think-pair-share technique has succeeded in improving students' reading comprehension Keywords: Think-Pair-Share, Reading Comprehension, Classroom Action Research